2016
DOI: 10.1002/ejsp.2209
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social diversity and neighbourhood attachment: The role of intergroup ties and affective appraisals of the environment. Evidence from Poland

Abstract: This paper investigates the relationship between perceived ethnic, age and income diversity and neighbourhood attachment, accounting for measures of objective diversity calculated for small, individualised neighbourhoods. With data from Warsaw in Poland, we examine whether neighbourhood ties with people of different ethnicity, age and income moderate the relationship between perceived diversity and attachment. We also test affective appraisals of the environment (excitement and irritation) as a mediator betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 59 publications
(87 reference statements)
1
19
0
1
Order By: Relevance
“…Indeed, past research examining aspects of neighbourhood diversity (in terms of categorical differences of ethnicity, socioeconomics, age, etc.) has highlighted the importance of including the perceived environment as a mediator of the objective environmental context on outcomes such as attitudes towards immigration, (Newman, Velez, Hartman, & Bankert, 2015), social cohesion (Koopmans & Schaeffer, 2016), and place attachment (Toruńczyk-Ruiz & Lewicka, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, past research examining aspects of neighbourhood diversity (in terms of categorical differences of ethnicity, socioeconomics, age, etc.) has highlighted the importance of including the perceived environment as a mediator of the objective environmental context on outcomes such as attitudes towards immigration, (Newman, Velez, Hartman, & Bankert, 2015), social cohesion (Koopmans & Schaeffer, 2016), and place attachment (Toruńczyk-Ruiz & Lewicka, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One of the novel aspects of the papers presented here is that the results were obtained with a wide range of previously unexplored outcome variables including out‐group negativity, support for minority group rights and neighbourhood affect. It also presented the first study examining different dimensions of diversity (i.e., ethnic, age and income diversity) within the same environment (Toruńczyk‐Ruiz & Lewicka, ).…”
Section: Discussionmentioning
confidence: 99%
“…Toruńczyk‐Ruiz and Lewicka () present an analysis of perceived diversity at the neighbourhood level and its effects on neighbourhood attachment in Poland. Their research is among the first to examine the impact of ethnic diversity together with two additional relevant sources of heterogeneity at the neighbourhood level—age and income diversity.…”
Section: Overview Of the Current Special Issuementioning
confidence: 99%
“…Past studies have revealed that these factors are associated with differences in residents' satisfaction with their physical environment [2,44,45] and all three place relationship dimensions-place attachment [6,13,46], social interaction [45,47], and community participation [11,48]. Homeownership has also been linked with the three place relationship dimensions, particularly place attachment [6,8,49] and community participation [8,10]. In these three communities, the percentage of homeownership was above 95%, similar to that of public housing in Taiwan as a whole [50].…”
Section: Study Sitesmentioning
confidence: 90%